The influence of light intensity on larval stages of snubnose pompano Trachinotus blochii Lacepede 1801 - Alejos, Marlon S. (College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2015)
Light can have significant impacts on larval stage of many marine fish species. Three studies were conducted to investigate the influence of light intensity on larval stages of snubnose pompano Trachinotus blochii. Study 1 and 2 were conducted to determine the influence of continuous illumination at different light intensities and increasing light intensities provided continuously on feeding, growth and survival of early stage snubnose pompano larvae from 1 to 10 DPH. Study 3 was conducted to determine the influence of continuous illumination at different light intensities on growth, survival and metamorphosis of late stage snubnose pompano larvae from 16 to 35 DPH. Five treatments with three replicate each were compared in all the studies. In study 1 and 3, treatment includes : T1 (indoor-natural photoperiod, 12 hL : 12 hD), T2 (500 lx, 24 hL), T3 (1000 lx, 24hL), T4 (2000 lx, 24hL) and T5 (3000 lx, 24hL). In study 2, treatments includes : T1 (indoor-natural photoperiod, 12hL : 12hD), T2 (300-500lx, 24hL), T3 _300-1000 lx, 24hL, T4 (300-2000 lx, 24hL) and T5 (300-3000 lx, 24hL). For study 1 and 2, newly hatched larvae were stocked at a density of 15 ind. /L and fed with enriched rotifers (Brachionus plicatilis : 50-250 um) at a density of 30 ind. /ml starting from 2 DPH. The number of rotifers in the digestive organ, feeding incidence and total length of larvae were exmined at 3 hours interval from 0400H to 2200H at 3 DPH, at 6 hours interval from 4 to 5 DPH and once at 8 DPH at 1000H. Final growth and survival were also determined after the experiment. For study 3, larvae were fed with the combination of artemia (Instar I ; 400-600 um) and artificial diet three times a day from 16 to 35 DPH. Morphological observation and growth assessment were done daily using stereo microscope. Survival was determined by counting all remaining fish after 35 DPH. Results indicate that snubnose pompano larvae are visual feeders and exhibit diet rhythm with the presence of 24 hours light. In contrast, larvae at natural photoperiod (12 hL : 12hD) normally undergoes diurnal rhythms. In study 1, better larval feeding, growth and survival were obtained at 500 lx. Larvae at higher light densities (2000 and 3000lx) did not survive and mass mortality occurred at 4 DPH while few remained at 1000 lx. In study 2, better and consistent larval feeding and higher survival was obtained at medium increasing light intensities (300-500 lx). However, greater larval growth was achieved at higher increasing light intensities (300-1000lx, 300-2000 lx, 300-3000 lx). In study 3, better growth, survival and significantly higher percentage of metamorphosed larvae was achieved at 3000 lx. Larvae at natural photoperiod (12hL : 12hD) had the lowest growth and survival in all experiments. Studies suggest that light intensity can improve feeding, growth, survival and metamorphosis of snubnose pompano larvae.